Analisis Kadar Timbal (Pb) di Dalam Ginjal Mencit (Mus musculus) yang Dipapar Secara Oral - Baehaki, Farhan; Riyanto, Agus; Luthfiah, Nur Afifah; Adelin, Azalia; Prahasta, Vivo; Rismayanti, Siti Nur (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2025)
Lead is a type of heavy metal that is harmful to health, including the kidneys. Lead can enter the body through several ways, including food and drink. This study was conducted to determine the effect of oral lead exposure on lead levels in the kidneys. The study was conducted with a post-test only control group design. The samples used were 8 male mice divided into 4 groups and given oral exposure to lead acetate at doses of 0.5 ppm, 1 ppm, and 2 ppm for 21 days. Measurement of lead levels was carried out using an Atomic Absorption Spectrophotometer (AAS) at a wavelength of 283.3 nm. It can be seen from the overall lead exposure at concentrations of 0.5 ppm, 1 ppm, and 2 ppm, that lead deposited in the kidneys increased by 68.67%. At a dose of 0.5 ppm, lead levels in the kidneys were 0.313 ppm (an increase of 9.38%). At a dose of 1 ppm, the lead level in the kidneys was 0.399 ppm (an increase of 39.38%). At a dose of 2 ppm, the lead level in the kidneys was 0.483 ppm (an increase of 68.67%). The average level of Pb absorbed in the kidneys increased along with the increase in lead entering the body.